ANALYSIS OF KNOWLEDGE LEVEL, ATTITUDE, AND MANAGEMENT BEHAVIOR TOWARD FINANCIAL: A CASE STUDY OF MICRO AND SMALL INDUSTRY IN JAMBI CITY - Suryani, Arna; Herianti, Eva (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research was conducted to analyze the level of knowledge, attitude, and management behavior toward financial. The primary data is taken from interview and questionnaire to the respondents of micro and small industry (UMK) in Jambi city. The data is analyzed descriptively by using scale range counting the score frequency of each question and counting score every component the research. From the results obtained, this confirmed that level of knowledge, attitude and management behavior toward finance of UMK in Jambi is categorize as high. The higher knowledge, attitude and management behavior toward financial show that individuals are able to comprehend the basic knowledge of personal financial which consists of basic things related to the use of financial management. UMK in Jambi city are able to learn and implement the knowledge, attitude, and management behavior toward financial to provide added value. Decision making and resource management, financial management is useful in order to run the business continuously. The UMK in Jambi city are demanded to have general knowledge of financial, financial management knowledge, saving and investment knowledge, risk and insurance knowledge and credit and debt knowledge in order to be able implement the better financial planning to get the best decision. Keywords: Knowledge, Attitude, Financial Management Behavior